Predictors of Insulin Resistance in Children versus Adolescents with Obesity - Yvette E. Lentferink; Marieke A. J. Elst; Catherijne A. J. Knibbe; Marja M. J. van der Vorst (Journal of Obesity)
Introduction. Obesity is a risk factor to develop metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM). Insulin resistance (IR) plays a major part in both. With increasing incidence of childhood obesity, this retrospective study aimed to identify predictors of IR in children/adolescents with obesity to optimize screening for IR. Method. Patients aged ≥ 2–≤ 18 years with obesity (BMI-SDS > 2.3) were included. IR was defined as HOMA-IR ≥ 3.4, and MetS if ≥3 of the following criteria were present: waist circumference and blood pressure ≥ 95th age percentile, triglycerides ≥ 1.7 mmol/l, HDL < 1.03 mmol/l, and fasting plasma glucose ≥ 5.6 mmol/l. Results. In total, 777 patients were included. Of the 306 children, 51, 38, and 0 were diagnosed with IR, MetS, and T2DM, respectively. Of the 471 adolescents, 223, 95, and 0 were diagnosed with IR, MetS, and T2DM, respectively. In the multivariable regression model, BMI-SDS, preterm birth, and Tanner stage were associated with IR in children (6.3 (95% CI 1.3–31.1), 5.4 (95% CI 1.4–20.5), 2.2 (95% CI 1.0–4.8)), and BMI-SDS and waist circumference in adolescents (4.0 (95% CI 1.7–9.2), 3.7 (95% CI 1.5–9.4)). Conclusion. Different IR predictors were observed in children/adolescents with obesity. These predictors can be used to optimize screening for IR in pediatric populations.